Validity of Acute Physiology and Chronic Health Evaluation (APACHE) IV for the Prediction of Prolonged Intensive Care Unit (ICU) Length of Stay in Dr. Sardjito General Hospital in the COVID Era - Muhammad Mufti Sofyanoor; Widyastuti, Yunita; Juni Kurniawaty; Djayanti Sari (HM Publisher, 2023)
Introduction: APACHE IV was a good predictor of ICU length of stay in the USA and some countries outside the USA but poor in others. It is important to develop a scoring system for the Indonesian population, especially in this scope, Dr. Sardjito General Hospital. To develop such a scoring system, it is reasonable to study the validity of APACHE IV in ICU Dr. Sardjito General Hospital for predicting prolonged length of stay. Methods: A retrospective cohort observational study using data from January 1st, 2020, to December 31st, 2020, taken from the ICU of Dr. Sardjito General Hospital. The data are the patient's observed ICU LOS and data required in calculating APACHE IV score and ICU LOS prediction. Discrimination is calculated using the area under (AUC) the receiver operating characteristic curve (ROC) and calibration by the Hosmer-Lemeshow test. Results: Samples were 329 patients. APACHE IV ICU length of stay prediction showed moderate discriminatory ability (AUC-ROC: 0.74) and poor calibration (p <0.001) to predict prolonged ICU stay. The APACHE IV score has a strong discriminatory ability (AUC-ROC: 0.83). Using the DeLong method, the AUC from ROC APACHE IV score was greater than the AUC from ROC predicted length of stay in APACHE IV ICU (p <0.001). APACHE IV predicted ICU length of stay overestimated observed ICU length of stay. Conclusion: APACHE IV ICU length of stay prediction has moderate discrimination and poor calibration to predict prolonged ICU stay. The APACHE IV score has better discrimination than the APACHE IV ICU length of stay prediction in predicting prolonged ICU stay.